2020
DOI: 10.1371/journal.pone.0238503
|View full text |Cite
|
Sign up to set email alerts
|

The anti-neuroinflammatory effects of Clinacanthus nutans leaf extract on metabolism elucidated through 1H NMR in correlation with cytokines microarray

Abstract: Clinacanthus nutans (CN) (Acanthaceae) is well-known for its anti-inflammatory properties among Asian communities; however, there are currently no data specifically focused on the anti-inflammatory effects of CN on the brain tissue. Neuroinflammation is a common consequence of toxin intrusion to any part of the central nervous system (CNS). As an innate immune response, the CNS may react through both protective and/or toxic actions due to the activation of neuron cells producing pro- and/or anti-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The induction of either 10 μl phosphate buffer saline (PBS) to the normal rat groups or lipopolysaccharides (LPS, 1 μg/1 μl) to the neuroinflammed groups have been described in previously published manuscripts ( Ahmad Azam et al, 2019 ; Ahmad Azam et al, 2020a ). To summarize, the rats were anesthetized with ketamine-xylazine (K-X); K: 80 mg/kg BW; X: 10 mg/kg of BW through intraperitoneal (i.p) route and they underwent stereotaxic surgery with a single intracerebroventricular (ICV) injection at the location of substantia nigra at the right side of the brain with a consistent rate of 3 μl per minute using a Harvard Apparatus Pump 11 elite infusion syringe via a Hamilton syringe (Holliston, Massachusetts, United States).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of either 10 μl phosphate buffer saline (PBS) to the normal rat groups or lipopolysaccharides (LPS, 1 μg/1 μl) to the neuroinflammed groups have been described in previously published manuscripts ( Ahmad Azam et al, 2019 ; Ahmad Azam et al, 2020a ). To summarize, the rats were anesthetized with ketamine-xylazine (K-X); K: 80 mg/kg BW; X: 10 mg/kg of BW through intraperitoneal (i.p) route and they underwent stereotaxic surgery with a single intracerebroventricular (ICV) injection at the location of substantia nigra at the right side of the brain with a consistent rate of 3 μl per minute using a Harvard Apparatus Pump 11 elite infusion syringe via a Hamilton syringe (Holliston, Massachusetts, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Clinacanthus nutans (CN) extracts (CNE) are well known for their anti-inflammatory activities ( Pongphasuk et al, 2005 ; Khoo et al, 2018 ). Extensive studies in a comprehensive metabolomics setting via proton nuclear magnetic resonance ( 1 H NMR) analysis have successfully elucidated the ameliorative effects of CNE treatments in the serum ( Ahmad Azam et al, 2019 ) and brain ( Ahmad Azam et al, 2020a ) of lipopolysaccharide (LPS)-induced neuroinflammed rats. The use of integrative omics between metabolomics and cytokines microarray (genomics) on brain tissue has resulted in the proposed ameliorating effects of CN treatment in an LPS-induced rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Isoschaftoside and clinacoside B as well as clinacoside C are known to be strong antioxidants, while the former was also reported to exert hepatoprotective abilities [9]. Isoschaftoside, a major component of Abrus mollis extracts, exhibited hepatoprotective potential against carbon tetrachloride (CCL 4 )-induced hepatic fibrosis in a rat model [51].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, it is known as "Sabah Snake Grass" or "Belalai Gajah" [8]. This medicinal plant has demonstrated a range of pharmacological activities, including anti-inflammatory, anti-carcinogenic and antimicrobial effects [9]. The leaves of C. nutans possessed antioxidant as well as anti-cancer potential towards tumorbearing mice [10].…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to an effect of its components, glyceryl 1,3-disterate, kaempferol 3- O -feruloyl-sophoroside 7- O -glucoside, and hydroxypthioceranic acid, which showed pro-surviving Bcl-2 and pro-apoptotic Bax expression activities [ 30 ]. Clinacanthus nutans aqueous extracts could reduce LPS-induced increase in proinflammatory IL-1β expression but increase anti-inflammatory IL-2 and IL-4 expression in brain tissue after oral administration in rats [ 105 ]. A recent study showed that C. nutans leaf, but not stem, extracts had a significant effect in reducing 7-kecoholesterol-induced brain endothelial cell death and suppressed inflammatory responses in endothelial cells, including reducing IL-1β, IL-6, IL-8, TNF-α, and COX-2 expression [ 106 ].…”
Section: Clinacanthus Nutans Extracts On Inflammatory Pathwa...mentioning
confidence: 99%